Analisis Debit Dengan Metode F.J. Mock Dan NRECA Serta Perbandingannya Terhadap Debit Pos Duga Air - M. Agussalim; Indriyanti Azis; Sukmasari Antaria; Riswal K; Annisa Febrianti; Ayu Rosdiana (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
The Makawa river basin located in the Rongkong watershed has an increase in surface flow which affects the discharge flow which can cause flooding. Therefore, discharge data is needed to manage existing water resources. This study aims to analyze the water discharge using the F.J. Mock and NRECA methods, which are then compared to the water estimation post discharge. The results of this study showed that the F.J. Mock method has a relative error of 48% and a correlation coefficient of 0,690 with a strong interpretation, while NRECA showed a relative error of 50% and a correlation coefficient of 0,669 with a strong interpretation. Therefore, it is concluded that the F.J. Mock method is more appropriate than the NRECA method with lower relative error results, and a higher correlation coefficient than NRECA. The result of the simulation discharge between F.J. Mock, NRACA and water estimation post discharge are quite far apart.